The invisible women of war examining the impact of the Marawi Siege on the lives of Muslim women placed at the intersection of widowhood and internal displacement - Alqaseer, Shebana C.
This study explored the impact of the 2017 Marawi Siege on women at the intersection of widowhood and displacement, with the aim of illuminating their experiences and lived realities as a view of the siege "from below," and providing corresponding recommendations for post- conflict rehabilitation and recovery. It employed a life histories approach informed by grounded theory and feminist standpoint theory, analyzing narratives gathered through interviews along a framework build on an understanding of conflict as experienced, conflict as a continuum, and conflict as intersectional. Key themes surfaced include recollections of life prior to the siege, the personal and social dimensions of loss, the economic impacts of war and widowhood, the psychosocial needs arising from the widows' experience, the role of institutions in mediating the impacts of war and widowhood, and the aspirations of Marawi's widows moving forward. Informed by these themes, the study offered specific policy recommendations from the macro to the micro levels, along with a reconceptualization of the women, peace, and security framework that emphasizes meaningful participation and empowerment of women premised on an understanding of peace as experienced, peace as a continuum, and peace as intersectional.